Assessment of the soil CO2 gradient method for soil CO2 efflux measurements: Comparison of six models in the calculation of the relative gas diffusion coefficient - Natchaya Pingintha (2018)
This paper uses a refined soil gradient method to estimate soil CO2 efflux. Six different models are used to determine the relative gas diffusion coefficient (ξ). A weighted harmonic averaging is used to estimate the soil CO2 diffusion coefficient, yielding a better estimate of soil CO2 efflux. The resulting soil CO2 efflux results are then compared to the soil CO2 efflux measured with a soil chamber. Depending on the choice of ξ model used, the estimated soil CO2 efflux using the gradient method reasonably approximates the efflux obtained using the soil chamber method. In addition, the estimated soil CO2 efflux obtained by this improved method is well described by an exponential function of soil temperature at a depth of 0.05 m with the temperature sensitivity (Q10) of 1.81 and a linear function of soil moisture at a depth of 0.12 m, in general agreement with previous findings. These results suggest that the gradient method is a practical cost-effective means to measure soil CO2 emissions. Results from the present study suggest that the gradient method can be used successfully to measure soil CO2 efflux provided that proper attention is paid to the judicious use of the proper diffusion coefficient. © 2009 The University of Georgia Journal compilation © 2010 Blackwell Munksgaard.